Identifying issues and implementing strategies - Skelton, Kathy; Combating Prejudice in Schools Project (Richmond, Vic.) (Richmond, Vic. : Clearing House on Migration Issues, 1985)
Aims, achievements, findings of project; strategies for schools.
Keywords: Prejudices -- Study and teaching -- Australia; Minorities -- Education -- Australia; Discrimination in education -- Australia; Education - Skills and curriculum - Cultural awareness; Education - Indigenous studies; Education - Schools; Education - Teaching; Victoria (Vic)